Single-molecule imaging of cholesterol-dependent cytolysin assembly - Senior, M (2015)
Cholesterol-dependent cytolysins (CDCs) are amongst the primary virulence factors for several important pathogens. Their typical function is to lyse cells by forming large pores in target membranes, often up to 40 nm in diameter and comprised of around 30-50 subunits. Pores assemble from diffusing monomers bound to the target membrane, via a prepore intermediate. Previous work on the mechanism of pore assembly has focused on structural and ensemble fluorescence information, complemented by atomic force microscopy. The experiments described herein present the application of single-molecule total internal reflection fluorescence microscopy to the study of CDC assembly, using droplet interface bilayers as a felicitous in vitro system. This technique supported millisecond temporal resolution imaging of CDC monomers and individual CDC complexes assembling in parallel. The recorded videos enabled quantification of assembly kinetics and further insight into the governing mechanism of assembly.